180k views
5 votes
Find the derivative of the function by using the Product Rule. Simplify your answer. f(x) = (x - 3)(x + 3)

2 Answers

6 votes

Answer:


f'(x)=2x

Explanation:

To Find :Find the derivative of the function by using the Product Rule. Simplify your answer. f(x) = (x - 3)(x + 3)

Solution :


f(x) = (x - 3)(x + 3)

We will use chain rule of product

Formula :
uv=u * v' +v \tyimes u'

=
(x-3) * 1+(x+3) * 1

=
(x-3)+(x+3)

=
2x

So,
f'(x)=2x

Hence the derivative of the function by using the Product Rule is 2x

User Torp
by
5.3k points
2 votes

Answer:


f'(x)=2x

Explanation:

Given : Function
f(x)=(x-3)(x+3)

To find : The derivative of the function by using the Product Rule ?

Solution :

The product rule of derivative is


(d)/(dx)(u\cdot v)=uv'+vu'

Here, u=x-3 and v=x+3


(d)/(dx)((x-3)\cdot (x+3))=(x-3)(d)/(dx)(x+3)+(x+3)(d)/(dx)(x-3)


(d)/(dx)((x-3)\cdot (x+3))=(x-3)1+(x+3)1


(d)/(dx)((x-3)\cdot (x+3))=x-3+x+3


(d)/(dx)((x-3)\cdot (x+3))=2x

Therefore,
f'(x)=2x

User Tehshin
by
4.9k points